Techniques for fixing mandibular fractures: an integrative literature review - Lima , Maria Vitória Araújo (2022)
In the face mandibular fractures, there are some fixation techniques, among which the Champy Technique stands out. These techniques have the same objective, which is to stabilize the fracture, restoring function and health to the patient. For the development of a correct behavior and obtaining a good result, it is essential to have adequate knowledge of the techniques. This article aims to report the research carried out in the literature regarding fixation techniques. It was an integrative literature review carried out through searches in the LILACS database. The inclusion criteria were articles in Portuguese and English and published between 2015 and 2021. Theses, books, dissertations, abstracts, course completion papers and studies that were not complete on the topic were excluded. Eleven articles were selected, which met the inclusion and exclusion criteria. Trauma is the major cause of mandibular fractures, which are the most common when compared to other facial structures. Its diagnosis and treatment must be appropriate to be able to restore it in a functional and aesthetic way, as incorrect treatments can cause sequelae. Mandibular fractures appear more frequently in the routine of maxillofacials, who perform interventions through fixation techniques in order to restore the function, esthetics and anatomy of the affected region, with emphasis on the Champy technique.